Enhanced Prefrontal Neuronal Activity and Social Dominance Behavior in Postnatal Forebrain Excitatory Neuron-Specific Cyfip2 Knock-Out Mice - Zhang, Yinhua; Kang Hyae, Rim; Lee, Seung-Hyun; Kim, Yoonhee; Ma, Ruiying; Jin, Chunmei; Lim, Ji-Eun; Kim, Seoyeon; Kang, Yeju; Kang, Hyojin; Kim, Su Yeon; Kwon, Seok-Kyu; et al. (Frontiers in Molecular Neuroscience, 2020)
The cytoplasmic FMR1-interacting protein 2 (CYFIP2) gene is associated with epilepsy, intellectual disability, and developmental delay, suggesting its critical role in proper neuronal development and function. CYFIP2 is involved in regulating cellular actin dynamics, and also interacts with RNA-binding proteins. However, the adult brain function of CYFIP2 remains unclear because investigations thus far are limited to Cyfip2 heterozygous (Cyfip2+/-) mice owing to perinatal lethality of Cyfip2-null mice. Therefore, we generated Cyfip2 conditional knock-out (cKO) mice with reduced CYFIP2 expression in postnatal forebrain excitatory neurons (CaMKII-Cre). We found that in the medial prefrontal cortex (mPFC) of adult Cyfip2 cKO mice, CYFIP2 expression was decreased in both layer 2/3 (L2/3) and layer 5 (L5) neurons, unlike the L5-specific CYFIP2 reduction observed in adult Cyfip2+/- mice. Nevertheless, filamentous actin (F-actin) levels were increased only in L5 of Cyfip2 cKO mPFC possibly because of a compensatory increase in CYFIP1, the other member of CYFIP family, in L2/3 neurons. Abnormal dendritic spines on basal, but not on apical, dendrites were consistently observed in L5 neurons of Cyfip2 cKO mPFC. Meanwhile, neuronal excitability and activity were enhanced in both L2/3 and L5 neurons of Cyfip2 cKO mPFC, suggesting that CYFIP2 functions of regulating F-actin and excitability/activity may be mediated through independent mechanisms. Unexpectedly, adult Cyfip2 cKO mice did not the display locomotor hyperactivity or reduced anxiety observed in Cyfip2+/- mice. Instead, both exhibited enhanced social dominance accessed by the tube test. Together, these results provide additional insights into the functions of CYFIP2 in the adult brain.